IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DALAM KURIKULUM MERDEKA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMAS BINA PUTERA-KOPOv - Dirjo, Dirjo; Ilzamudin, Ilzamudin; Hidayat, Wahyu; Lugowi, Rifyal Ahmad; Wasehudin, Wasehudin (FIKRAH, 2023)
In implementing an independent curriculum, educators are expected to be able to meet the learning needs of each student with different characteristics. To realize the expected learning objectives of differentiated learning is the right idea. But the facts show that it is still rare for teachers to be willing to work on this because they do not have a clear concept to carry it out. This study aims to fulfill the implementation of differentiated learning in Islamic Religious Education subjects at SMAS Bina Putera-Kopo. This research uses descriptive qualitative research methods. Research that uses hypothesis testing through data on words compiled, and data can be compiled for analysis using narrative descriptions. This study found that in an effort to implement differentiation, the following steps are needed; first, planning is carried out by mapping the initial abilities of students, what must be learned is interest and readiness to learn and determine essential material in learning outcomes; Second, it performs three components, namely the differentiation of content, processes, and products. Third, conduct an evaluation to determine the effectiveness and success rate of the objectives of the learning carried out. The researcher concluded that differentiation learning in Islamic Religious Education subjects provides an opportunity to learn naturally, starting from the initial ability of each student. The success of differentiated learning implementation is obtained due to the support of good communication and collaboration between both parties, namely the school and parents.